Political risk guarantees and capital flows: The role of bilateral investment treaties - Wasseem Mina (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
In this paper the author empirically examines whether the influence of bilateral investment treaties' political risk guarantees extends to other types of capital flows - FDI, private debt, public debt and portfolio equity. The paper uses panel data on middle and low income countries during the period 1984 - 2011 and adopts LSDV estimation methodology to account for heterogeneity arising from unobserved country, region, and time effects. The paper finds that ratified BITs with OECD countries increase FDI flows and reduce private debt flows. They also tilt the composition of capital flows in favor of FDI. The novelty of the paper stems from its extension of the examination BITs influence beyond FDI and the distinction between private and public debt flows. The paper contributes to the FDI and capital flows literatures.
Keywords: F21; F34; G15; G18; K33; 330; political risk; bilateral investment treaties; capital flows; debt flows; equity flows